Usable Pasts - Tuleja, Tad (Utah State University, University Libraries, 1997)
In Usable Pasts, fourteen authors examine the manipulation of traditional expressions among a variety of groups from the United States and Canada: the development of a pictorial style by Navajo weavers in response to traders, Mexican American responses to the appropriation of traditional foods by Anglos, the expressive forms of communication that engender and sustain a sense of community in an African American women's social club and among elderly Yiddish folksingers in Miami Beach, the incorporation of mass media images into the ""C&Ts"" (customs and traditions) of a Boy Scout troop, the changing meaning of their defining Exodus-like migration to Mormons, Newfoundlanders' appropriation through the rum-drinking ritual called the Schreech-In of outsiders' stereotypes, outsiders' imposition of the once-despised lobster as the emblem of Maine, the contest over Texas's heroic Alamo legend and its departures from historical fact, and how yellow ribbons were transformed from an image in a pop song to a national symbol of ""resolve.""